A Systematic Review: Problems in Learning Chemistry Practicum of Merdeka Curriculum - Nur Azizah; Endang Widjajanti Laksono (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2025)
This research aims to identify chemistry practicum problems in implementing the merdeka curriculum. The research method used is systematic literature review (SLR) by analyzing the results of relevant research from the Google Scholar and ERIC databases, as many as 10 articles based on their suitability for the research topic in the last five years (2021-2025). Through this method, a systematic review of articles is carried out by following predetermined steps. The results of this systematic literature review (SLR) found a total of seven problems originating from students, teachers, and practicum facilities. These problems include students lack of understanding of practicum procedures, teachers difficulties in assessing student performance, teachers limitations in presenting interesting and contextualized chemistry practicum, teachers low ability to make practicum teaching media, teachers low understanding of the use of small-scale practicum, limited practicum equipment, and lack of chemistry practicum guidebooks. These problems indicate the need to improve teacher skills, develop teaching materials, and provide adequate practicum facilities.